2022
DOI: 10.1039/d1ra09231f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and functionalization of biocompatible carboxymethyl chitosan/gelatin membranesviaanodic electrophoretic deposition

Abstract: A biocompatible CMC/G membrane for titanium substrates has been fabricated in an eco-friendly manner and could be a promising carrier for negatively charged agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…The results validated that free neutral surfaces (-CH 3 and -OH) led to greater chondrogenic induction extent but less protein adsorption, cell spreading, and adhesion than charged surfaces (-NH 2 and -COOH) [182]. Negatively charged carboxymethyl chitosan-gelatin (CMCG) composite membranes fabricated via anodic electrophoretic deposition (AED) have demonstrated their ability to transport drugs or other medical agents containing negative charges, which suggested that CMCG membranes could act as a strong candidate for surface functionalised biomaterials with negative charges [183]. The ε-poly-L-lysine (EPL) and phenylboronic acid (PBA)-modified gelatin methacrylamide hydrogels (GelMA-EPL and GelMA-EPL/B) synthesised via Michael addition reaction exhibited positive surface charges, significantly promoting adsorption of negatively charged PGs and secreted PGs in the solution and hence providing a good 3D microenvironment for cartilage repair with improved biocompatibility [184].…”
Section: Surface Chargementioning
confidence: 99%
See 2 more Smart Citations
“…The results validated that free neutral surfaces (-CH 3 and -OH) led to greater chondrogenic induction extent but less protein adsorption, cell spreading, and adhesion than charged surfaces (-NH 2 and -COOH) [182]. Negatively charged carboxymethyl chitosan-gelatin (CMCG) composite membranes fabricated via anodic electrophoretic deposition (AED) have demonstrated their ability to transport drugs or other medical agents containing negative charges, which suggested that CMCG membranes could act as a strong candidate for surface functionalised biomaterials with negative charges [183]. The ε-poly-L-lysine (EPL) and phenylboronic acid (PBA)-modified gelatin methacrylamide hydrogels (GelMA-EPL and GelMA-EPL/B) synthesised via Michael addition reaction exhibited positive surface charges, significantly promoting adsorption of negatively charged PGs and secreted PGs in the solution and hence providing a good 3D microenvironment for cartilage repair with improved biocompatibility [184].…”
Section: Surface Chargementioning
confidence: 99%
“…The hydrophobic surface modified with -NH 2 and -CH 3 suppressed the MDA-MB-231 cell adhesion and proliferation, inducing cell apoptosis, and mitochondria-mediated apoptosis by suppressing the phosphatase and TENsin homolog deleted on chromosome 10 (PTEN)/phosphoinositide 3-kinase (PI3K)/Ak strain transforming (AKT) pathway. Negatively charged CMCG composite membranes on titanium (Ti) substrates were produced via the AED-inhibited cell apoptosis of human BMSCs [183]. The presence of gelatin provided some degree of hydrophobic nature for the composite.…”
Section: Surface Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation